1994
DOI: 10.1149/1.2054936
|View full text |Cite
|
Sign up to set email alerts
|

Poisoning and Activation of the Gold Cathode during Electroreduction of  CO 2

Abstract: Table I, Adhesion strength of copper layer prepared on a glass substrate. Cu thickness Method (l~m) Adh. strength (kg/2 mmC]) Fe-Ni wire AI pull stud ~ Sputtering Glass/Cr/Cu 2.0 10.1 >6.0 b Electroless plating Glass/Cu 0.5 -0 -1.0 ~ Electroless plating Glass/ZnO/Cu 2.0 10.8 >6.0 b Electroless plating Glass/TiOJCu 0.5 -0 -1.0 c a Epoxy coated aluminum pull studs with 2.7 mm~ were used for the adhesion strength tests. These values were converted into kg/2 mmC].b In these tests, the interface between the aluminu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 0 publications
7
54
1
1
Order By: Relevance
“…It was experimentally observed that the CO signal is restored to its initial value only after potential excursion to higher potential (close to 1.0 V), but the subsequent polarization at negative values for CO 2 reduction leads to the same signal behavior of deactivation. This deactivation or poisoning of gold during the CO 2 electroreduction to CO was also observed by Kedzierzawski et al 71 Based on the results of cyclic voltammetry, conducted after experiments of polarization for CO 2 electroreduction, they stated that adsorbed CO is not the cause of the observed deactivation of the gold electrode. Some other adsorbed reaction intermediate, that suffers electrochemical oxidation at potentials higher than that for CO, is likely to be the reason for such observed deactivation.…”
Section: Electrochemical Experiments Electrocatalytic Reduction Of Cosupporting
confidence: 73%
“…It was experimentally observed that the CO signal is restored to its initial value only after potential excursion to higher potential (close to 1.0 V), but the subsequent polarization at negative values for CO 2 reduction leads to the same signal behavior of deactivation. This deactivation or poisoning of gold during the CO 2 electroreduction to CO was also observed by Kedzierzawski et al 71 Based on the results of cyclic voltammetry, conducted after experiments of polarization for CO 2 electroreduction, they stated that adsorbed CO is not the cause of the observed deactivation of the gold electrode. Some other adsorbed reaction intermediate, that suffers electrochemical oxidation at potentials higher than that for CO, is likely to be the reason for such observed deactivation.…”
Section: Electrochemical Experiments Electrocatalytic Reduction Of Cosupporting
confidence: 73%
“…At −0.70 V, CO production on polycrystalline Au foil electrodes operated in native C i electrolytes commences with ~60% Faradaic efficiency but declines to ~10% over the course of 2 hours (Figure 2A, black squares, error bars shown in Figures 2-4 are the standard deviation of three independent measurements) consistent with literature reports. 32,34 The large error bars observed for electrolyses performed in native C i electrolyte reveal a high degree of run-to-run variability, consistent with trace metal impurities strongly influencing catalytic efficiency. Catalyst deactivation for CO production is accompanied by a rise, from ~23% to ~77%, in Faradaic efficiency for the hydrogen evolution reaction (HER).…”
Section: Resultsmentioning
confidence: 90%
“…[23][24][25][26][27][28][29][30][31] However, planar group 11 metal surfaces are known to lose their catalytic activity and selectivity for CO 2 reduction over the time scale of minutes to hours under steady state electrolysis. 22,[32][33][34][35][36][37] For example, copper surfaces lose one-half of their catalytic activity for methane production within 20 min of polarization, 33,35 and CO production selectivity on Au 32 and Ag 34 decreases within minutes of electrolysis. Despite posing a clear obstacle to practical implementation of CO 2 reduction technologies, the mechanistic basis for this activity loss remains poorly understand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, to address such problem, the electrocatalytic activity of metal electrodes is enhanced prior to their use; the enhancement is based on thermal, 4 chemical, 5 cathodic 6 (application of a potential at which hydrogen is generated), and anodic treatment 1,2,7,8 (formation of metal oxide and its subsequent reduction). In particular, multiple anodic treatments of metal electrodes offer highly enhanced electrocatalytic activity, which even enables one to observe substantial currents of hydrogen sorption and desorption at Au electrodes.…”
mentioning
confidence: 99%